Performance of Agro-Morphology and Genetic Parameter of 12 Rice Genotypes at Lowland Rice Irrigation - Bambang Sutaryo (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2014)
ABSTRACTResearch to study performance of agro-morfology and genetic parameters of twelve rice genotypes at lowland rice irrigation was conducted at Giripeni, Kulon Progo, Yogyakarta, during the wet season of November 2011 to February 2012. Twelve rice genotypess, namely Inpari 1, Inpari 2, Inpari 3, Inpari 4, Inpari 5, Inpari 6, Inpari 7, Ciherang, Dodokan, Silugonggo, Situ Bagendit, and IR64 were arranged in a randomized complete block design in three replications. Seedling of 15 days was planted in legowo 4:1, with one seedling per hill, spacing of 25 x 12,5 x 50 cm, in plot size of 5 x 10 m2. Time application and dosage of fertilizer were :1) Three days before planting with 2 t/ha organic, 2) Five days after planting with 300 kg/ha Phonska, 3) At 21 days after planting with 100 kg Urea/ha; and 4) At 35 days after planting with 100 kg Urea/ha. Data indicated that Inpari 3, Inpari 5 and Inpari 1 yielded 7.55; 7.44; and 6.98 t ha -1 respectively, and significantly higher than that of the best check variety Ciherang (6.26 t ha-1 ). Broad genetic variabilities were found for grain yield, panicle number per hill, filled grain per panicle, and total grain per panicle. High heritability estimate was found for 1000-grain weight, filled grain per panicle, total grain per panicle, panicle number per hill, plant height, and maturity. Genetic and phenotypic correlation between filled grain per panicle and yield, total grain per panicle and yield, and panicle number per hill and yield showed significantly different.Key words : agro-morphology, genetic parameter, rice genotype, lowland irrigation